The Role of the Innate Immune System in Granulomatous Disorders - Petersen, Helen J.; Smith, Andrew M. (Frontiers in Immunology, 2013)
The dynamic structure of the granuloma serves to protect the body from microbiological challenge. This organised aggregate of immune cells seeks to contain this challenge and protect against dissemination, giving host immune cells a chance to eradicate the threat. A number of systemic diseases are characterised by this specialised inflammatory process and granulomas have been shown to develop at multiple body sites and in various tissues. Central to this process is the macrophage and the arms of the innate immune response. This review seeks to explore how the innate immune response drives this inflammatory process in a contrast of diseases, particularly those with a component of immunodeficiency. By understanding the genes and inflammatory mechanisms behind this specialised immune response, will guide research in in the development of novel therapeutics to combat granulomatous diseases.